The Effects of Working Memory Capacity, Types of Instructions, and Recall on Following Instructions Performance - Mohamad Azhari, Abu Bakar; Kartini, Abd Ghani; Norehan, Zulkiply (Human Resource Management Academic Research Society (HRMARS), 2025)
Many past studies showed that participants performed well during spoken instructions task with action recall. The discussion was directed to understand the functional role of working memory components. However, less studies investigated the role of Working Memory Capacity (WMC) in following instructions. Therefore, this study aimed to investigate the effect of WMC, types of instructions, and recall in following instructions based on the total correct recall. We recruited 52 participants (26 with high WMC and 26 with low WMC) who completed spoken and written instruction tasks, followed by verbal and action recall. This quasi-experimental design used three-way mixed factorial design (2x2x2), and all data were analysed by using three-way factorial ANOVA. Findings of this study suggested that there is a significant effect of WMC, types of instructions, and types of recall on following instructions performance. The results also reveal that there is a significant interaction between WMC and types of instructions, and between types of instructions and types of recall. One of the main results suggests that both groups (WMC) performed better during action recall compared to verbal recall in both types of instructions.